Processing pathway of Escherichia coli 16S precursor rRNA. - Srivastava, A K (1989)
Immediate precursors of 16S rRNA are processed by endonucleolytic cleavage at both 5' and 3' mature termini, with the concomitant release of precursor fragments which are further metabolized by both exo- and endonucleases. In wild-type cells rapid cleavages by RNase III in precursor-specific sequences precede the subsequent formation of the mature ends; mature termini can, however, be formed directly from pre-16S rRNA with no intermediate species. The direct maturation is most evident in a strain deficient in RNase III, and the results in whole cells are consistent with results from maturation reactions in vitro. Thus, maturation does not require cleavages within the double-stranded stems that enclose mature rRNA sequences in the pre-16S rRNA.